Enhancement potentials for labour efficiency in small and large scale cattle farms - Nagy, Tibor (Acta Agraria Debreceniensis, 2001)
The author examined the possibilities of increasing the labour efficiency at 6 large-scale farms and at 109 small-scale farms in Hajdú-Bihar county. He stated that the level of labour efficiency was higher for large scale farms than for small-scale farms. However, there is potential for work organisation of milking, feeding and other jobs on the large-scale farms, too. The reason for the low labour efficiency on small-scale dairy farms is the small number of livestock, obsolete machinery, and lack of expertise. The author points out that the quality of raw milk is also an important issue. Using examination methods of work organisation, he determined the critical points of raw milk production.